The Impact of Advertising Attractiveness, Event Promotion, and Discount Prices on Product Purchase Decisions on Instagram @promomedan.id - Hendra Jonathan Sibarani; Anjeli; Justin Adi Putra Pasaribu (Kusuma Negara Business School, 2021)
abstract